Local Human Resource Development Strategy in Facing Industry 4.0 for The Economic Welfare of The Community in Medan City - Muhammad Anshar; Mierna Zulkarnain; Rani Rahim (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
The Industrial Revolution 4.0 brings significant transformations in the global production and economic system through the integration of digital technology, artificial intelligence, and automation. Medan City, as one of the main economic centers in Sumatra, faces serious challenges in preparing its local human resources (HR) to face these changes. This study aims to identify the skills gap of local HR in Medan City in the context of Industry 4.0 needs and provide policy recommendations to improve the competitiveness of local HR. The research method uses a mixed-method approach by combining quantitative methods through a survey of 100 local workers and qualitative methods through in-depth interviews with 10 key stakeholders. The results show that only 23% of respondents have a good understanding of Industry 4.0 technology, and 67% have basic digital literacy skills but only 18% have advanced skills. The highest skills gaps are in data analysis and big data interpretation (78%), programming (71%), and cybersecurity (69%). This study formulates an Integrated HR Development Model consisting of 5 main pillars: adaptive formal education, competency-based vocational training, multi-stakeholder collaboration, lifelong learning, and soft skills development. The implementation of the strategy is projected to increase the employability rate by 45%, reduce unemployment from 6.8% to 4.2%, increase average income by 25-35%, and create 15,000-20,000 new jobs in a 5-year period.